Preclinical Evaluation of In Vitro and In Vivo Antiviral Activities of KCT-01, a New Herbal Formula against Hepatitis B Virus. (4th July 2018) - Kim, Hong; Jang, Eungyeong; Kim, So-Young; Choi, Ji-Yoon; Lee, Na-Rae; Kim, Dae-Sung; Lee, Kyung-Tae; Inn, Kyung-Soo; Kim, Bum-Joon; Lee, Jang-Hoon
Abstract : Hepatitis B virus (HBV) infectious diseases currently remain incurable due to limitations of conventional antivirals such as incapability of eradicating HBV DNA, prolonged use, drug resistance, and virological relapse. KCT-01, a 30% ethanol extract consisting of Artemisia capillaris, Sanguisorba officinalis, and Curcuma longa, was newly developed. The objective of this study was to investigate pharmacological activities of KCT-01 against HBV using HepG2.2.15 cells and a hydrodynamic injection model. KCT-01 significantly lowered antigen secretion, virion production, and pgRNA synthesis in HepG2.2.15 cells without affecting cell viability. KCT-01 administration also resulted in significant decrease of serum virion production, liver covalently closed circular (ccc) DNA levels, and mRNA synthesis of cytokines in the liver of mice injected with HBV DNA hydrodynamically. Interestingly, coadministration of KCT-01 with entecavir enhanced its in vitro and in vivo antiviral activities. Moreover, safety of KCT-01 was assured up to 5000 mg/kg in rats in both single and repeated-dose preclinical studies. Taken together, our findings demonstrate that KCT-01 is capable of suppressing HBV replication and inflammatory cytokine production in in vitro and in vivo models without showing toxicity, suggesting the potential of using KCT-01 alone or in combination with entecavir as antiviral agent.